2023
DOI: 10.21203/rs.3.rs-2428259/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Too healthy for their own good: Orthorexia nervosa and compulsive exercise in the community

Abstract: Background The similarities and differences between the orthorexia nervosa symptoms (ONs) and the symptoms and correlates of eating disorders listed in the DSM-5 need to be elucidated. ONs were examined in a volunteer community sample in conjunction with compulsive exercise, disordered eating, as well as emotional and behavioral correlates of eating disorders. Methods Participants were 561 adult volunteers (93 men, 17.09%) aged 19–72 (M = 32.7 ± 11), recruited via social media networks. Participants self-re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The protective role of positive body experiences in this study was observed both indirectly as well as directly, as some variance was also accounted for by the positive body experiences down-moderating the in uence of compulsive exercise on ONs. Since ONs and compulsive exercise seem to be synergic [10], it is possible that positive body experiences dampen this positive feedback loop.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The protective role of positive body experiences in this study was observed both indirectly as well as directly, as some variance was also accounted for by the positive body experiences down-moderating the in uence of compulsive exercise on ONs. Since ONs and compulsive exercise seem to be synergic [10], it is possible that positive body experiences dampen this positive feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study identi ed some positive body experiences as being protective against ON, it must be noted that their contribution is considerably weaker than that of known risk factors. Risk factors, such as compulsive exercise, disordered eating, emotion dysregulation, insecure attachment and parental feeding practices account for even more of the variance in ONs [10]. The relative weakness of protective vs risk factors for orthorexia is disappointing since targeting protective factors is an effective strategy in prevention programs [31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations